2019
DOI: 10.33549/physiolres.934159
|View full text |Cite
|
Sign up to set email alerts
|

Opioid and Endocannabinoid System in Orofacial Pain

Abstract: Orofacial pain disorders are frequent in the general population and their pharmacological treatment is difficult and controversial. Therefore, the search for novel, safe and efficient analgesics is an important but still elusive goal for contemporary medicine. In the recent years, the antinociceptive potential of endocannabinoids and opioids has been emphasized. However, concerns for the safety of their use limit their clinical applications. the possibility of modulating the activity of endocannabinoids by reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…In recent years, the interconnection between the endogenous antinociceptive systems has been the focus of growing attention. 130 A role for the opioid system in cannabinoid antinociception has been demonstrated, as has the reverse. 131,132 This is not surprising because the endogenous elements composing these systems share the same pattern of anatomic distribution and have comparable functional properties.…”
Section: Naaa Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the interconnection between the endogenous antinociceptive systems has been the focus of growing attention. 130 A role for the opioid system in cannabinoid antinociception has been demonstrated, as has the reverse. 131,132 This is not surprising because the endogenous elements composing these systems share the same pattern of anatomic distribution and have comparable functional properties.…”
Section: Naaa Inhibitorsmentioning
confidence: 99%
“…136,137 Of interest, especially regarding migraine-related pain, is the fact that the pathways of both systems are involved in the modulation of brainstem descending control of trigeminal nociception. 130 For example, blockade of both opioid and CB1 receptors led to a significant reduction in anandamide-mediated antinociception. 98 Moreover, CB2 receptor activation caused release of β-endorphin from keratinocytes, thereby inducing antinociception.…”
Section: Naaa Inhibitorsmentioning
confidence: 99%
“…Studies have reported that peripherally acting opioids significantly attenuate inflammatory and neuropathic pain ( Tiwari et al, 2016 , 2018 ; Bruce et al, 2019 ). Notably, peripherally acting opioids attenuate pain involving the dopaminergic and endocannabinoid systems, which require further intensive study ( Zubrzycki et al, 2019 ; Vaidya et al, 2021 ). Interactions between immune cell-derived EOPs and PORs also provide novel insights into pharmaceutical development and alternative strategies for orofacial pain treatment.…”
Section: Strategies For Orofacial Pain Controlmentioning
confidence: 99%
“…Multi-faceted pathophysiology and psychosocial comorbidity often challenges the correct diagnosis and management of OFP. Traditionally, OFP is treated using (a) medications such as non-steroidal anti-inflammatory drugs, local anesthetics, muscle relaxants, endocannabinoids, anti-convulsants, and antidepressants [ 7 , 8 , 9 ]; (b) oral appliances such as occlusal splints [ 10 ]; (c) massage therapy [ 11 ]; and (d) diode-laser therapy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%